Digital Meeting Job Sheet Innovation: An Effort to Enhance Administrative Task Performance Among Vocational Students - Chantyka Abelva Azzahra; Andi Basuki; Erna Sukmawati (Transpublika Publisher, 2026)
Students’ ability to prepare meeting agendas, invitations, minutes, attendance lists, and meeting documents is an important component of Administrative Task Performance in the MPLB curriculum. This research and development project aims to produce a Digital Meeting Job Sheet through validation by subject matter experts and media experts to improve Administrative Task Performance in the Meeting Management module for Grade 11 MPLB 2 students at SMKN 1 Malang. This research and development project employs the ADDIE model: Analyze, Design, Develop, Implement, and Evaluate. The pilot study involved 30 Grade 11 MPLB 2 students at SMKN 1 Malang. Data analysis techniques involved comparing the average performance percentages of students before and after using the media to assess improvements in administrative skills. The resulting media features interactive step-by-step guidance, industry-standard document templates, and learning materials, along with integrated email sending functionality, developed using Google Apps Script to ensure accessibility via digital devices. The research results indicate that validation by subject matter experts and media experts confirmed the media is highly suitable for use, and there was a significant improvement in students’ Administrative Task Performance regarding meeting management elements following the use of the media in instruction. This media requires periodic updates in line with advancements in office automation technology to remain relevant to the demands of the professional workplace.